2016
DOI: 10.1038/srep29783
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between intestinal epithelial cells and immune cells in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) involves functional impairment of intestinal epithelial cells (IECs), concomitant with the infiltration of the lamina propria by inflammatory cells. We explored the reciprocal paracrine and direct interaction between human IECs and macrophages (MΦ) in a co-culture system that mimics some aspects of IBD. We investigated the expression of intercellular junctional proteins in cultured IECs under inflammatory conditions and in tissues from IBD patients. IECs establish functional ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 44 publications
3
67
0
1
Order By: Relevance
“…3). Moreover, it has been reported that the increased expression and/or production of different inflammatory cytokines can facilitate the breaking of the intestinal subepithelial basement membrane, and thus promote the presence of activated mononuclear cells in close proximity to the intestinal epithelial cells [25]. Such situation may lead to the disruption of junctional complexes in the mucosal epithelium, as evidenced in the present study, by the decrease in the expression of ZO-1 (zonula occludens) and/or TFF-3 (trefoil factor) in the experimental models of colitis ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…3). Moreover, it has been reported that the increased expression and/or production of different inflammatory cytokines can facilitate the breaking of the intestinal subepithelial basement membrane, and thus promote the presence of activated mononuclear cells in close proximity to the intestinal epithelial cells [25]. Such situation may lead to the disruption of junctional complexes in the mucosal epithelium, as evidenced in the present study, by the decrease in the expression of ZO-1 (zonula occludens) and/or TFF-3 (trefoil factor) in the experimental models of colitis ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the role of Carlr in the macrophage-enterocyte interaction, we assessed the localization of Carlr in the intestinal cell line Caco2 at steady state and in the presence of LPS and activated THP-1 cells. This cell line is widely used as a model for human intestinal inflammatory diseases and is able to produce NF-κB regulated cytokines such as IL-6 (2426). Caco2 cells showed nuclear localization of Carlr at basal conditions, however, when co-culturing the intestinal cells with LPS or with activated THP-1 cells, resembling the intestinal inflammatory environment, we saw that Carlr expression was increased and at the same time translocated to the cytoplasm, mainly in the co-culture condition (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of alterations in tight junction proteins are key players in epithelial barrier function in inflammatory bowel diseases is rapidly enhancing our understanding of critical mechanisms in disease pathogenesis as well as novel therapeutic opportunities. The disruption of integrity of the epithelial barrier may intrigue the onset of inflammatory bowel diseases[15]. The leaky intestinal epithelial barrier is mainly attributed to defects of the TJs and IEC loss[14]; the deficient TJs are the primary cause for the compromised intestinal epithelial barrier[3].…”
Section: Resultsmentioning
confidence: 99%